Effects of release parameters on flight distance in the javelic ball throw as an event leading to the javelin throw - Maeda, M. (Japan Journal of Physical Education, Health and Sport Sciences, 2019)
The javelic ball throw using a JaveBall is a track and field event designed for elementary schoolchildren and is regarded as an introduction to the javelic throw, an event for junior high school students, which in turn is an introduction to the javelin throw, an event for high school students and beyond. This study examined the effect of release parameters on flight distance in the javelic ball throw. Flight distances and release parameter values of 146 throws by 17 participants were measured. Initial velocity was the parameter with the strongest influence on flight distance. Release angle, angle of attack, and horizontal angle of attack had some influence, but flight distance did not differ markedly even when the values of these parameters were very low or very high. The ratio of the actual flight distance to the theoretical flight distance decreased with increasing initial velocity, indicating that achieving a greater actual distance becomes more difficult as the release velocity increases. Although the rotational speed of the JaveBall around its longitudinal axis was a factor that reduced the actual flight distance relative to the theoretical flight distance regardless of its magnitude, it was considered that the decrease in the actual flight distance relative to the theoretical flight distance will decrease when an extremely small rotational speed is applied without reducing the initial velocity. Although the javelic ball throw is intended as an introduction to the javelic throw, which in turn leads to the javelin throw, this study showed that the characteristics of the JaveBall are not necessarily similar to those of a javelin, for which the rotational speed increases relative to the increase in initial velocity. Athletes and their coaches should be aware of this if they expect to transition from the javelic ball throw to the javelin throw in the future.